Effects of longJterm lisinopril therapy on central and peripheral hemodynamics in patients with dilated cardiomyopathy - Z. T. Astakhova; T. M. Gatagonova; L. M. Mosin; O. T. Kotsoeva; A. S. Plieva; L. V. Osipova (Российский кардиологический журнал, 2008)
The study was aimed at investigating the effects of a second?generation ACE inhibitor, lisinopril (Diroton), on central and peripheral hemodynamics in patients with dilated cardiomyopathy (DCMP). In total, 39 persons with DCMP and chronic heart failure (CHF), aged 35–55 years, were examined. Diroton dose was titrated from low (2,5 mg/d) to high (10 mg/d). The treatment lasted for 12 months. Longterm Diroton therapy, as a part of complex pharmaceutical treatment, was associated with significant improvement in total and regional hemodynamics in DCMP patients: left ventricular ejection fraction increased, dilated myocardium volumes and sizes reduced, together with reduction in temporal rheography parameters and increase in velocity ones. Diroton therapy also improved clinical course of CHF and circadian blood pressure profile.